2022
DOI: 10.1155/2022/6420865
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on the Pharmacological Action of Schisantherin A

Abstract: Schisantherin A (Sch A) is a dibenzocyclooctadiene lignan monomer isolated from the fruit of Schisandra chinensis (Turcz.) Baill. (S. chinensis). At present, many studies have shown that Sch A has a wide range of pharmacological effects, including its anti-Parkinson and anti-inflammatory effects and ability to protect the liver, protect against ischemia-reperfusion (I/R) injury, suppress osteoclast formation, and improve learning and memory. Its mechanism may be related to the antioxidant, anti-inflammatory, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 96 publications
(113 reference statements)
0
3
0
1
Order By: Relevance
“…Schisantherin A is an active substance isolated from the fruit of Schisandra chinensis (Turcz.) Baill., a perennial deciduous woody liana with antiparkinsonian, anti-inflammatory, hepatoprotective, ischemia–reperfusion injury prevention and osteoclast formation inhibition effects ( Xiao et al., 2022 ). The hepatoprotective effects of schisantherin A may be achieved by improving gut inflammation and modulating the gut microbiota ( Yu S. et al., 2022 ).…”
Section: Plant Natural Products Ameliorate Mafld By Regulating the Gu...mentioning
confidence: 99%
“…Schisantherin A is an active substance isolated from the fruit of Schisandra chinensis (Turcz.) Baill., a perennial deciduous woody liana with antiparkinsonian, anti-inflammatory, hepatoprotective, ischemia–reperfusion injury prevention and osteoclast formation inhibition effects ( Xiao et al., 2022 ). The hepatoprotective effects of schisantherin A may be achieved by improving gut inflammation and modulating the gut microbiota ( Yu S. et al., 2022 ).…”
Section: Plant Natural Products Ameliorate Mafld By Regulating the Gu...mentioning
confidence: 99%
“…Основной группой биологически активных веществ извлечений из плодов лимонника китайского (Schizandra chinensis) являются лигнаны (схизандрины), которые способствуют увеличению активности супероксиддисмутазы, обеспечивают шунтирование потока электронов в дыхательной цепи [9,10].…”
Section: обсуждение результатовunclassified
“…Various in vitro and in vivo studies have found them to demonstrate various antioxidative, anti-inflammatory, anticancer, and antiviral properties, among others. For example, S. chinensis has an inhibitory effect on cytochrome P450, family 3, subfamily A (CYP3A), and P-glycoprotein (P-gp), which can mediate metabolism or efflux of substrates, and may interact with many drugs [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. In addition, Nasser et al [ 9 ] described various biological properties of schisandrin B.…”
Section: Introductionmentioning
confidence: 99%